2018
DOI: 10.3889/oamjms.2018.062
|View full text |Cite
|
Sign up to set email alerts
|

Value of SSTR2A and Claudin - 1 in Differentiating Meningioma from Schwannoma and Hemangiopericytoma

Abstract: BACKGROUND:The distinction between meningioma, schwannoma and solitary fibrous tumour/ hemangiopericytoma can be challenging in some cases. This study evaluates the expression of Somatostatin receptor 2A (SSTR2A) and Claudin-1 in these different tumours.MATERIAL AND METHODS:Thirty-five cases of meningioma, 10 cases of intracranial schwannoma and 10 cases of hemangiopericytoma were assessed. The immunohistochemical expression of SSTR2A and Claudin-1 was evaluated and scored according to the percentage of immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Somatostatin receptor 2A was found to be a more sensitive diagnostic marker for meningioma than epithelial membrane antigen-a conventional meningioma marker (40). Since then, accumulating evidence has emerged to support the diagnosis value of SSTR2A as it is a highly sensitive and specific marker for meningioma (41,42). A case report has shown that SSTR2A, combined with epithelial membrane antigen, provides assistance for the diagnosis of an unusual skull tumor with psammomatoid bodies (43).…”
Section: Sstr2-related Diagnosis Approaches For Meningiomamentioning
confidence: 99%
“…Somatostatin receptor 2A was found to be a more sensitive diagnostic marker for meningioma than epithelial membrane antigen-a conventional meningioma marker (40). Since then, accumulating evidence has emerged to support the diagnosis value of SSTR2A as it is a highly sensitive and specific marker for meningioma (41,42). A case report has shown that SSTR2A, combined with epithelial membrane antigen, provides assistance for the diagnosis of an unusual skull tumor with psammomatoid bodies (43).…”
Section: Sstr2-related Diagnosis Approaches For Meningiomamentioning
confidence: 99%
“…Interestingly both were also negative for SSTR2a, the most reliable meningioma marker. However, it has been previously reported that although all Grade 1 and 2 meningiomas are positive for SSTR2A, this is true for only 20% of Grade 3 meningiomas [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Schwannomas demonstrated notably low or absent 68 Ga-DOTATATE uptake, concordant with tissue studies demonstrating absence of SSTR expression in schwannomas by immunohistochemical staining. 16 For neuroaxis tumors with indeterminant MRI features and absent 68 Ga-DOTATATE uptake, schwannoma should be a primary consideration. All schwannomas ranged from an SUV max of 1 to 8.5.…”
Section: Discussionmentioning
confidence: 99%